الثورة الروسية عام 1917 (Journal of the College of Basic Education, 2019)
The Russian Revolution of 1917, or the Bolshevik Revolution, was one of the most important historical events in Europe during the First World War. This revolution changed the course of Russian history. Its outbreak led to the formation of the Soviet Union, which was dismantled in the late 20th century. Because of a number of popular unrest and protests against the rule of Russian tsars and the Russian Empire, whose reign was characterized by the slow development of the country because of the existence of a political system subject to autocratic regimes and the control of nobles and landlords in all aspects of life in Russia, made the Russian society in the late century Nineteen rural people in the majority of workers and peasants, with the influence of the clergy and the imperial palace, accompanied by a primitive social structure, a backward economy and an autocratic government. Life in Russia was in the style of the Middle Ages. Russia retreated from the European industrial revolution until 1860, This led the people to wage a revolt against the Russian reactionary tsarist government in 1917. It was one of the most famous leaders of the Russian Revolution, Vladimir Lenin, who was called the " Revolutionaries of this revolution the Bolsheviks name or Almnschwk means the majority.